Ayodhya verdict: Bad theology, without justice - Arunima, G. (2010)
One of the most damaging consequences of the recent judgment by the Allahabad High Court on the dispute over the Babri Masjid is that it has provided a legal cover for a subtle shift from devasthana (holy place) to janmasthana (birthplace). It also lays the legal ground for converting the imagined birthplace of a diery into property claims which trump other claims to the same property. It thus opens a dangerous door to majoritarianism in India. - Reproduced.
Keywords: Ayodhya; Religion